Penerapan Syarat Sah Perjanjian dan Prinsip Syariah terhadap Perjanjian Asuransi Syariah: (Studi Kasus Anik Melawan PT Asuransi Jiwa Generali Indonesia) - Mohamad Yuflih Huda Maheswara (Jurnal Hukum Lex Generalis, 2022)
In the midst of the flourishing of the sharia insurance industry, there are also many lawsuits for default. This study will analyze the application of the legal terms of the agreement based on the KUHPer and the application of sharia insurance contracts in the sharia insurance industry in Indonesia by taking the case study of Anik against PT Asuransi Jiwa Generali Indonesia. As for analyzing the case, a descriptive explanation is used which aims to construct the extent to which the sharia insurance agreement applies the legal requirements of the sharia insurance agreement and contract. Thus, the author recommends strengthening supervision which is analyzed using the juridical-normative method.